Transcriptome analysis of fat accumulation in 3T3-L1 adipocytes induced by chlorantraniliprole - Chen, Ge; Wang, Ge; Xu, Weidong; Xiao, Ying; Peng, Ye (Frontiers in Nutrition, 2022)
Introduction Chlorantraniliprole is a diamide insecticide widely used in agriculture. Chlorantraniliprole has been previously found to increase the accumulation of triglycerides (fats) in adipocytes, however, the underlying molecular mechanism is unknown. The present study aimed to explore the molecular mechanisms of chlorantraniliprole-induced fat accumulation in 3T3-L1 adipocytes. Methods We measured the triglyceride content in chlorantraniliprole-treated 3T3-L1 adipocytes, and collected cell samples treated with chlorantraniliprole for 24 h and without any treatment for RNA sequencing. Results Compared with the control group, the content of triglyceride in the treatment group of chlorantraniliprole was significantly increased. The results of RNA sequencing (RNA-seq) showed that 284 differentially expressed genes (DEGs) were identified after treatment with chlorantraniliprole, involving 39 functional groups of gene ontology (GO) and 213 KEGG pathways. Moreover, these DEGs were significantly enriched in several key genes that regulate adipocyte differentiation and lipogenesis including Igf1, Rarres2, Nr1h3, and Psmb8. Discussion In general, these results suggest that chlorantraniliprole-induced lipogenesis is attributed to a whole-gene transcriptome response, which promotes further understanding of the potential mechanism of chlorantraniliprole-induced adipogenesis.